The Spatial Distribution of mtDNA and Phylogeographic Analysis of the Ant Cardiocondyla kagutsuchi (Hymenoptera: Formicidae) in Japan - Ichiro Okita; Kaori Murase; Toshiyuki Sato; Kimihiko Kato; Akihiro Hosoda; Mamoru Terayama; Keiichi Masuko (Sociobiology)
In this study, we investigated the geographical distribution of haplotypes of Cardiocondyla kagutsuchi Terayama in Japan using COI/II mitochondrial DNA. We also examined their genealogy with C. kagutsuchi in other areas and their close relative species. Four haplotypes were found. While two of them were found in a limited area (Ishigaki and Okinawa Islands) separately, the others were distributed widely across Honsyu, Shikoku, and Kyusyu areas in Japan. The newly invaded area by C. kagutsuchi in Japan was Shizuoka prefecture. Their haplotype of Shizuoka were the same as the two haplotypes of the Honsyu, Shikoku, and Kyusyu areas. The haplotype network showed that the two haplotypes were distant from each other. The distance between them was 33, even though the two haplotypes are distributed in the same area. From the phylogenetic tree that we constructed, we found that C. strigifrons was in the same clade as C. kagutsuchi.